A comprehensive investigation on thermal management of large‐capacity pouch cell using micro heat pipe array. (8th August 2019) - Mo, Xiaobao; Hu, Xuegong; Tang, Jinchen; Tian, Hong
Summary: A proper and effective battery thermal management system (BTMS) is critical for large‐capacity pouch cells to guarantee a suitable operating temperature and temperature difference. Hence, in this paper, a micro heat pipe array (MHPA) is utilized to build the thermal management system for large‐capacity pouch cells. In order to study the property of BTMS in depth, experimental and numerical investigation are carried out by considering the C‐rate, working medium, air velocity and duty. The experimental results present that the T max can be maintained below 43.7°C and the Δ T is below 4.9°C at the discharge rate of 3C in the battery module with MHPA‐liquid. Moreover, the T max of the battery module with MHPA‐liquid falls as the air velocity increases. The simulation results show that the variation and distribution of temperature matched well with experimental results. It demonstrates that the MHPA‐based BTMS is viable and effective for large‐capacity pouch cell battery, even at high C‐rate and cycle duty. Abstract :